Granulite-facies metamorphism, fluid buffering and partial melting in the Buffels River area of the Namaqualand metamorphic complex, South Africa - McStay, Jonathan Hugh (Department of Geological Sciences, 2016)
The Buffels River area of central Namaqualand comprises a sequence of Proterozoic volcano-sedimentary gneisses intruded by granitoid orthogneisses. This study concentrates on the mechanisms of granrilite-facies metamorphism in a small area of isofacial rocks. Particular emphasis is placed on the role of partial melting and the infiltration and buffering of metamorphic fluid is examined.